Biomechanics applied to the long jump technique of the Paralympic medalist Kiara Rodríguez - Sangucho Hidalgo, Nelly Priscila; Rivadeneira Arias , Karla Natalia; Aguilar Morocho, Elva Katherine (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
Athletics is a time and mark sport that can be practiced individually or by teams and contains various modalities. Some of them can be adapted and generate participation as Paralympic sports. The objective of this study was to analyze if biomechanics can improve the long jump technique of the athlete with physical disabilities. For this, the Paralympic medalist Kiara Rodríguez was studied. The long jump execution technique was evaluated through the Kinovea software. The research was descriptive, analytical, and of a mixed type, applying a quantitative and qualitative analysis. The SPSS software was used to establish the normality statistic and the Ancova test, from which an abnormality value was obtained in the data of the kicked leg with a significance of p=0.07. which is less than 5%. In the analysis of covariance, a p value associated with f of 0.408 was obtained, which is greater than 5%, so f is not significant, accepting the null hypothesis that the technical gesture of the Paralympic athlete Kiara Rodríguez is deficient.